Control of the Immune Response by Pro-Angiogenic Factors - VORON, Thibault; MARCHETEAU, Elie; PERNOT, Simon; COLUSSI, Orianne; TARTOUR, Eric; TAIEB, Julien; TERME, Magali (Frontiers in Oncology, 2014)
The progressive conversion of normal cells into cancer cells is characterized by the acquisition of eight hallmarks. Among these criteria, the capability of the cancer cell to avoid the immune destruction is found. Thus, tumors develop mechanisms to become invisible to the immune system, such as the induction of immunosuppressive cells which are able to inhibit the development of an efficient immune response. Molecules produced in the tumor microenvironment are involved in the occurrence of an immunosuppressive microenvironment. Recently, it has been shown that Vascular Endothelial Growth Factor -A (VEGF-A) exhibits immunosuppressive properties in addition to its proangiogenic activities. VEGF-A can induce the accumulation of immature dendritic cells, myeloid derived suppressor cells, regulatory T cells and inhibit the migration of T lymphocytes to the tumor. Other proangiogenic factors such as Placental Growth Factor (PlGF) could also participate in tumor-induced immunosuppression, but only few works have been performed on this point. Here, we review the impact of proangiogenic factors (especially VEGF-A) on immune cells. Anti-angiogenic molecules, which target VEGF-A/VEGFR axis, have been developed in the last decades and are commonly used to treat cancer patients. These drugs have anti-angiogenic properties but can also counteract the tumor-induced immunosuppression. Based on these immunomodulatory properties, anti-angiogenic molecules could be efficiently associated with immunotherapeutic strategies in preclinical models. These combinations are currently under investigation in cancer patients.